The Effect of Learning Motivation on The Performance of Management Students at Nias Raya University in Completing Course Assignments - Lisitina Jalogo; Veronika Yunita F. Laia; Thomas F. Sarumaha; Feby Trias T. Daya; Arnold G. Giawa; Datathema Laia (Lembaga Penelitian, Penerbitan dan Pengabdian Kepada Masyarakat Institut Badri Mashduqi, 2026)
This study aims to examine the effect of learning motivation on the performance of Management students at Nias Raya University in completing course assignments. The research employed a quantitative approach with an associative research design. Data were collected through a structured questionnaire distributed to 30 active Management students selected using purposive sampling. The collected data were analyzed using simple linear regression after passing validity, reliability, and classical assumption tests, including normality, linearity, and heteroskedasticity tests. The results show that learning motivation has a positive and significant effect on student performance. The regression analysis indicates that an increase in learning motivation leads to an improvement in students’ ability to complete academic assignments. The t-test results confirm that learning motivation significantly influences student performance at a 5% significance level. Furthermore, the coefficient of determination reveals that learning motivation explains 83.8% of the variance in student performance, while the remaining percentage is influenced by other factors not examined in this study. These findings highlight the importance of fostering learning motivation to enhance student performance in higher education. Therefore, lecturers and educational institutions are encouraged to implement learning strategies that strengthen students’ motivation in order to improve academic outcomes.